Adaptation to flooding during emergence and seedling growth in rice and weeds, and implications for crop establishment - Ismail, Abdelbagi M.; Johnson, David E.; Ella, Evangelina S.; Vergara, Georgina V.; Baltazar, Aurora M. (Oxford University Press, 2012)
Direct seeding of rice is being adopted in rainfed and irrigated lowland ecosystems because it reduces labour costs in addition to other benefits. However, early flooding due to uneven fields or rainfall slows down seed germination and hinders crop establishment. Conversely, early flooding helps suppress weeds and reduces the costs of manual weeding and/or dependence on herbicides; however, numerous weed species are adapted to lowlands and present challenges for the use of flooding to control weeds. Advancing knowledge on the mechanisms of tolerance of flooding during germination and early growth in rice and weeds could facilitate the development of improved rice varieties and effective weed management practices for direct-seeded rice Rice genotypes with a greater ability to germinate and establish in flooded soils were identified, providing opportunities to develop varieties suitable for direct seeding in flooded soils. Tolerance of flooding in these genotypes was mostly attributed to traits associated with better ability to mobilize stored carbohydrates and anaerobic metabolism. Limited studies were undertaken in weeds associated with lowland rice systems. Remaining studies compared rice and weeds and related weed species such as Echinochloa crus-galli and E. colona or compared ecotypes of the same species of Cyperus rotundus adapted to either aerobic or flooded soils Tolerant weeds and rice genotypes mostly developed similar adaptive traits that allow them to establish in flooded fields, including the ability to germinate and elongate faster under hypoxia, mobilize stored starch reserves and generate energy through fermentation pathways. Remarkably, some weeds developed additional traits such as larger storage tubers that enlarge further in deeper flooded soils (C. rotundus). Unravelling the mechanisms involved in adaptation to flooding will help design management options that will allow tolerant rice genotypes to adequately establish in flooded soils while simultaneously suppressing weeds